Countryside in Jan Čep's Works - Komárek, Karel (Bohemica Olomucensia, 2012)
In the prose writings by Czech writer Jan Čep (1902-1974), the countryside is a significant content component which serves the author to express the central ideas. The source for Čep's depiction of countryside is his native countryside in Middle Moravia. Čep depicts the countryside realistically, in an objective way at first sight, yet at the same time he expresses the metaphysical dimension of the world and life.